Review on socioeconomic and sustainability of oil palm plantations among rural communities in Malaysia - Ahmad M.J.; Ismail R.; Ghani F.A. (Institute of Physics, 2024)
Malaysian oil palm plantations contributed 2.7% of Malaysian Gross Domestic Product (GDP) in 2020 and became the world's second largest producer of palm oil after Indonesia. Unfortunately, the expansion of oil palm plantations has always been linked to deforestation, greenhouse gas emissions, and soil erosion. Despite the negative environmental repercussions, there is no denying that the rapid expansion of oil palm plantations has had beneficial social and economic impacts. Therefore, in this study, researchers aim to review recent studies on the socioeconomic impacts of oil palm plantations in Malaysia for the last decade (2012 - 2022). This study also identifies challenges faced by rural communities who are participated in oil palm cultivation. Since this is a conceptual paper, secondary sources, such as research articles, government reports, and published research works, are used in this study. We employed desktop study method to search the academic papers and reports from online databases. Most the papers agreed that land development for oil palm enhances socioeconomic levels, especially among rural communities by providing job opportunities, creating small businesses, reducing poverty, and improving their livelihoods. However, the involvement of farmers and planters in oil palm downstream activities and multiple crop cultivation remains low since small-scale farmers highly depend on selling fresh fruit bunches (FFB) to get their income. The drop in crude palm oil prices because of the international market has severely affected oil palm smallholders' income. Most of previous research also believed sustainable oil palm plantation helps smallholders improve their socioeconomic conditions. The authorities may also make more efforts to promote sustainable plantations, especially among smallholders. Published under licence by IOP Publishing Ltd.